2013
DOI: 10.1186/gm440
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and outbreak investigation: from sequence to consequence

Abstract: Outbreaks of infection can be devastating for individuals and societies. In this review, we examine the applications of new high-throughput sequencing approaches to the identification and characterization of outbreaks, focusing on the application of whole-genome sequencing (WGS) to outbreaks of bacterial infection. We describe traditional epidemiological analysis and show how WGS can be informative at multiple steps in outbreak investigation, as evidenced by many recent studies. We conclude that high-throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 58 publications
1
75
0
Order By: Relevance
“…Genomic epidemiology has been increasingly applied to the study of epidemic-associated clonal variants of infectious agents to separate them from other related isolates (10,11). This field combines traditional epidemiological methods with genome sequence similarity analysis of bacterial isolates from patients and their potential reservoirs associated with different times and places.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic epidemiology has been increasingly applied to the study of epidemic-associated clonal variants of infectious agents to separate them from other related isolates (10,11). This field combines traditional epidemiological methods with genome sequence similarity analysis of bacterial isolates from patients and their potential reservoirs associated with different times and places.…”
mentioning
confidence: 99%
“…This approach was extensively applied, e.g., during the large multistate Escherichia coli O104:H4 epidemic (12). WGS will change the way we compare isolates because it allows for the analysis of all potential diversities and enables the detection of novelties associated with genome synteny, sequences, single genes, and polymorphisms between the isolates, as well as potential changes in the genomes that occur during infection (10,13). We recently found that only a few single-nucleotide polymorphisms (SNPs) are detected in C. jejuni after its intestinal passage through an infected patient (13).…”
mentioning
confidence: 99%
“…The most reliable variants for building such phylogenies are single-nucleotide polymorphisms (SNPs). Thus, core-genome SNP typing is currently the standard method for reconstructing large phylogenies of closely related microbes [45]. Currently, there are three paradigms for core-genome SNP typing based on read mapping, k-mer analyses, and wholegenome alignment.…”
mentioning
confidence: 99%
“…Recently, high-throughput DNA sequencing, particularly bench-top sequencing, has brought many new opportunities to this field (42)(43)(44)(45) and has allowed bacterial genomics to be integrated into what might be called "public health microbiology version 2.0" (v2.0) through WGS of cultured isolates to provide simultaneous information on organism identity, epidemiology, and antimicrobial therapy (Fig. 2).…”
Section: The Role Of Clinicogenomics In Public Health Microbiologymentioning
confidence: 99%